Pendidikan Agama Kristen Dalam Keluarga Berorientasi Pada Kehidupan Melalui Bed Stories - Yuel, Yuel (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2023)
This research is dotted with the phenomenon of family life in the GKE Buntut Bali Congregation, Malan Island District, Katingan Regency through Bedstories (bedtime stories). The purpose of this study is to describe the implementation of Christian Religious Education in life-oriented families through Bedstories (Bedtime Stories) in the GKE Buntut Bali congregation. This research uses descriptive qualitative methods with interview, observation, and documentation data collection techniques. Research findings reveal that generally parents in the GKE Hosanna Buntut Bali congregation have received bedtime stories from their predecessors, both fathers, mothers, grandfathers, and grandmothers. But only some of them are able to pass on to later generations, with categories always, rarely, not even doing so at all. The obstacles faced when telling stories before going to bed are the influence of technology, such as television and cellphones.